Perlindungan Hukum terhadap Pekerja Atas Manipulasi Data Kepesertaan BPJS Ketenagakerjaan dalam Program Jaminan Kehilangan Pekerjaan (JKP) - Rizqy Rahmansyah; Ilham Firmansyah; Bintang Alfina Wijayanti; Nanda Afaf Azzahra; Vivi Neiska Hendriana (Journal of Industrial Relations Studies, 2026)
This study aims to examine the legal obligations of employers in implementing the Job Loss Guarantee Program (JKP) based on the provisions of applicable laws and regulations and analyze the form of legal protection for workers in cases of manipulation of BPJS Ketenagakerjaan participant data in the program. The research method used is a normative juridical method with a statutory approach, through a review of legal regulations governing the implementation of the JKP Program and the protection of workers' rights against manipulation of BPJS Ketenagakerjaan participant data. The results of the study indicate that manipulation of participant data, such as changing the employment relationship status from termination of employment (PHK) to resignation, is a violation of workers' rights that can result in administrative and criminal sanctions. Legal protection for workers who are harmed can be achieved through administrative data correction, industrial relations dispute resolution, and criminal legal proceedings in the event of data falsification